LGBT DALAM TAKARAN SOSIOLOGI HUKUM - Musa Arifin (Yurisprudentia: Jurnal Hukum Ekonomi, 2016)
One of current controversial phenomenon which many people talk about in the society is the legalation of lesbian, gay, bisexual and transgender (LGBT) from government. The assertion from LGBT community comes along with bigger population  growth of LGBT communities.  The declaration done by these communities directed to be national attention by publicating with some big electronic media.